ANALISIS PENGATURAN POSISI TAP ON LOAD TAP CHANGER PADA TRANSFORMATOR DAYA 30 MVA 70/20 KV DI GI MAULAFA - Agusthinus S. Sampeallo; Wellem F. Galla; Darius M. K. Jala (Jurnal Media Elektro, 2019)
ABSTRACT The Maulafa substation is a sub-system in the electrical power distribution system in the city of Kupang, has two transformers of 30 MVA 70/20 kV each equipped with OLTC. OLTC installation aims to obtain a stable secondary voltage value despite the voltage drop on the primary side, this is because the tap changer works by changing the coil ratio in a transformer. The results of calculations and analyzes performed on transformer 1 OLTC, tap position is in position 9, with a voltage range of 20.94 kV at peak load, with a primary voltage of 69.12 kV. For the lowest load, it is in position 9 with a voltage range of 20.85 kV with a primary voltage of 68.81 kV. Whereas for transformer 2 the primary voltage is 69.08 kV for peak load and 68.91 kV for lowest load, being in position 2 for peak load and position 1 for lowest load, with a range of voltage of 21.19 kV and 20 respectively. 88 kV. The OLTC tap position of transformer 1 can still be reduced to position 6 with a voltage range of 20.21 kV for peak loads and 20.11 kV for the lowest loads. Both transformers have the same loading, both peak load and lowest load of 26 MW for peak load and 15 MW for lowest load. ABSTRAK Gardu Induk Maulafa merupakan sub sitstem dalam sistem penyaluran daya listrik yang ada di Kota Kupang, memiliki dua buah transformator masing-masing 30 MVA 70/20 kV yang dilengkapi dengan OLTC. Pemasangan OLTC yang bertujuan untuk mendapatkan nilai tegangan sekunder yang stabil meskipun terjadi drop tegangan pada sisi primer, hal ini dikarenakan tap changer bekerja dengan cara merubah perbandingan lilitan dalam sebuah transformator. Hasil perhitungan dan analisis yang dilakukan pada OLTC transformator 1, posisi tap berada pada posisi 9, dengan jangkauan tegangan 20,94 kV pada saat beban puncak, dengan tegangan primer sebesar 69,12 kV. Untuk beban terendah, berada pada posisi 9 dengan jangkauan tegangan sebesar 20,85 kV dengan tegangan primer sebesar 68,81 kV. Sedangkan untuk transformator 2 tegangan primernya sebesar 69,08 kV untuk beban puncak dan 68,91 kV untuk beban terendah, berada pada posisi 2 untuk beban puncak dan posisi 1 untuk beban terendah, dengan Jangkauan tegangan masing-masing 21,19 kV dan 20,88 kV. Posisi tap OLTC transformator 1 masih bisa diturukan ke posisi 6 dengan jangkauan tegangan sebesar 20,21 kV untuk beban puncak dan 20,11 kV untuk beban terendah. Kedua transformator memiliki pembebanan yang sama, baik beban puncak maupun beban terendah yakni 26 MW untuk beban puncak dan 15 MW untuk beban terendah.